Analisis Kepuasan Generasi Z terhadap Layanan E-Commerce: Implementasi Distribusi Binomial - Rahmadina, Alya Rahmadina; Raynara, Heickel; Purnama, Shine'on Najla; Ersa, Zahran (Jurnal Bisnis, Manajemen, dan Ekonomi, 2024)
This research aims to determine the probability of success in testing the quality of e-commerce services. The variables in this research consider the quality of e-commerce services and customer satisfaction, which are then grouped again based on dimensions. The dimensions of e-commerce services are product availability, delivery, and information and complaints. A binomial distribution is used to estimate the indicators in that dimension. Indicators in this dimension include product availability, delivery time, price and reliability, product quality and condition, customer complaints and return policies, and information quality. Success and samples were taken with n equal to 14 respondents as one representative of each study program. The population N is modeled using a binomial distribution by conducting n experiments. Each trial has two possible outcomes, namely success or failure. The probabilities of success and failure are expressed jointly by p and 1-p. The instrument used to collect data was a questionnaire with a Likert scale. The results of this research are p (strongly agree) = 0.191, p (agree) = 0.466, p (somewhat agree) = 0.269, p (disagree) = 0.046 and p (strongly disagree) = 0.027. Strongly agree, agree, and so on, state the respondent's answer to the statement about Shopee's service quality. The probability of success will increase when the sample size is smaller than a considerable probability value based on trials with varying n and x values.